Renal Sarcoidosis Presenting as Fanconi Syndrome - Suma Prakash; Kevin Lu; Rohit Gupta; Mithu Molla (Annals of Internal Medicine: Clinical Cases)
Fanconi syndrome is an extremely rare complication of renal sarcoidosis. We describe a case of biopsy-proven granulomatous interstitial nephritis secondary to sarcoidosis with the rare presenting feature of Fanconi syndrome. Our patient successfully received steroids initially, followed by mycophenolate and infliximab. These findings provide clinicians an important insight in recognizing this rare complication of sarcoidosis and opportunity to consider alternative regimens that can avoid or reduce side effects of first-line steroid therapy.